Arctic cloud macrophysical characteristics from CloudSat and CALIPSO - Liu, Yinghui; Key, Jeffrey R.; Ackerman, Steven A.; Mace, Gerald G.; Zhang, Qiuqing (DigitalCommons@University of Nebraska - Lincoln, 2012)
The lidar and radar profiling capabilities of the CloudSat and Cloud-Aerosol Lidar and Infrared Pathfinder (CALIPSO) satellites provide opportunities to improve the characterization of cloud properties. An Arctic cloud climatology based on their observations may be fundamentally different from earlier Arctic cloud climatologies based on passive satellite observations, which have limited contrast between the cloud and underlying surface. Specifically, the Radar–Lidar Geometrical Profile product (RL-GEOPROF) provides cloud vertical profiles from the combination of active lidar and radar. Based on this data product for the period July 2006 to March 2011, this paper presents a new cloud macrophysical property characteristic analysis for the Arctic, including cloud occurrence fraction (COF), vertical distributions, and probability density functions (PDF) of cloud base and top heights. Seasonal mean COF shows maximum values in autumn, minimum values in winter, and moderate values in spring and summer; this seasonality ismore prominent over the Arctic Ocean on the Pacific side. The mean ratios of multi-layer cloud to total cloud over the ocean and land are between 24% and 28%. Low-level COFs are higher over ocean than over land. The ratio of low-level cloud to total cloud is also higher over ocean. Middle-level and high-level COFs are smaller over ocean than over land except in summer, and the ratios of middle-level and highlevel clouds to total cloud are also smaller over ocean. Over the central Arctic Ocean, PDFs of cloud top height and cloud bottomheight show (1) two cloud top height PDF peaks, one for cloud top heights lower than 1200 mand another between 7 and 9 km; and (2) high frequency for cloud base below 1000 m with the majority of cloud base heights lower than 2000 m.